The Analysis Potency Grouper Fish Resources ( Plectropomus leopardus ) in Waters Regency Kolaka Southeast Sulawesi, Indonesia - Saleh, Ramlah; Adimu, Hasan Eldin; Landu, Anti; Fekri, Latifa (Yayasan Serumpun Karang Konservasi, 2024)
Grouper fish is one _ source of Power ecosystem reef corals that have marked economic highs. The objective Study is to analyze the potency source of grouper fish power in Regency Kolaka. A study was conducted in Regency Kolaka, a coastal area, and eyed fishermen's livelihood as fisherman grouper fishermen. Study This is held for eight months, i.e. April - November 2022. Grouper fish in the waters of Regency Kolaka has experienced excess catch by 70%. Based on these data, effort management needs to be done immediately for the continuity of grouper fish resources in the waters.